LEGAL AND CRIMINOLOGICAL ASPECTS OF RAPE WITH DATE RAPE DRUG - Aleksandra Nowak (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej)
Rape is a very serious offense, and the study of its victims indicates that they experience serious consequences of trauma. Nowadays more and more rape victims are intoxicated by special substances described as a ëdate rape drugí. Such a drug may be any psychoactive substance which switches off victimís free will in the area of undertaking a sexual intercourse and excludes defence against the perpetrator of the rape. In addition, ëdate rape drugí constitutes an obstacle during criminal investigation as it makes it more difficult to detect the perpetrator.